1997
DOI: 10.2508/chikusan.68.838
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Fatty Acid Composition and the Size of Adipocytes from Subcutaneous Adipose Tissue of Holstein Steers During the Fattening Period

Abstract: The fatty acid composition and the diameter of subcutaneous adipocytes from 13Holstein steers at different fattening stages were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The percentage of MUFA of marbling flecks categorized as L was significantly greater than M and S (P < 0.05), suggesting that larger marbling flecks tend to have a greater MUFA. Lending support to our findings, He et al (1997) reported that large adipocytes had greater MUFA, and Yang et al (2006) reported that the diameters of adipocytes in large marbling flecks were larger than those of small flecks on average.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The percentage of MUFA of marbling flecks categorized as L was significantly greater than M and S (P < 0.05), suggesting that larger marbling flecks tend to have a greater MUFA. Lending support to our findings, He et al (1997) reported that large adipocytes had greater MUFA, and Yang et al (2006) reported that the diameters of adipocytes in large marbling flecks were larger than those of small flecks on average.…”
Section: Resultssupporting
confidence: 88%
“…The fatty acid profile was measured according to the method of He et al (1997) as follows: the target marbling (approximately 10 mg) was scraped off using a metal spatula and methylated in 5 mL of methanol containing 5% hydrochloric acid for 3 h at 100°C. Adipose tissues of whole rib eye and subcutaneous fat were sampled by wiping the surface of the rib eye or fat with polyester plates 2.5 cm in width.…”
Section: Fatty Acid Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The fatty acid profile was determined according to the method of He et al (1997). In brief, approximately 10 mg of each adipose tissue sample were methylated in 3 mL of methanol containing 5% hydrochloric acid for 3 h at 100°C.…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…Cellular lipid accumulation in mature adipocytes depends on both lipogenesis and lipolysis and may alter cell size and the cellular fatty acid composition. It was found [33] that in growing and fattening beef cattle the composition of cellular monounsaturated fatty acids such as C14:1, C16:1 and C18:1 had strong positive correlation with mean size of adipocytes, while that of saturated fatty acids C18:0 and C16:0 had a negative correlation with it. A similar correlation was found between the cellular fatty acids composition and adipocytes distributed in the same fat pad that excluded variations caused by animal, feed and environment [34].…”
Section: Discussionmentioning
confidence: 99%